A review of spatial downscaling of satellite remotely sensed soil moisture. (18th April 2017) - Peng, Jian; Loew, Alexander; Merlin, Olivier; Verhoest, Niko E. C.
Abstract: Satellite remote sensing technology has been widely used to estimate surface soil moisture. Numerous efforts have been devoted to develop global soil moisture products. However, these global soil moisture products, normally retrieved from microwave remote sensing data, are typically not suitable for regional hydrological and agricultural applications such as irrigation management and flood predictions, due to their coarse spatial resolution. Therefore, various downscaling methods have been proposed to improve the coarse resolution soil moisture products. The purpose of this paper is to review existing methods for downscaling satellite remotely sensed soil moisture. These methods are assessed and compared in terms of their advantages and limitations. This review also provides the accuracy level of these methods based on published validation studies. In the final part, problems and future trends associated with these methods are analyzed. Key Points: Limitations of current downscaling methods and challenges ahead Need for intercomparison of different downscaling methods Opportunity for synthesis use of all data source for downscaling